Landuse/Cover Change Trend in Soroti District Eastern Uganda - Egeru, A; Majaliwa, M.G. J. (Journal of Applied Sciences and Environmental Management, 2009)
This study assessed the extent and trend of landuse/cover change in Soroti District, Uganda. A series of systematically corrected Orthorectified Landsat imageries of 1973, 1986 and 2001 were downloaded from the Landsat website. The images were analysed using unsupervised classification approach and the land-use/cover were validated and/or reconstructed by ground truthing, use of secondary data, and key informants. The study establishes that; small-scale farming was the major landuse type (24.2%) and grasslands were the dominant landcover unit (26.1%) in 1973. Small-scale farming however declined by 5.3% in 1986 due to prevailing insurgence at the time while grasslands gained by 2.9%. In 2001, small-scale farming had increased by 13.6% at the expense of woodlands (-2.3%), Bushlands(-5.5%), Forest stock (-2.2%) and wetlands (-0.44) that experienced declines. This drastic gain in small-scale farming is likely to treat negative environmental effects such as intensity of floods and droughts, soil nutrient and biodiversity loss due habitat conversion.
Keywords: Landuse; Cover Change Trend; Soroti District Eastern Uganda